Development of Website-Based Statistics Learning Videos - Dewi Juliah Ratnaningsih; Hasanah, Siti Hadijah (JTP - Jurnal Teknologi Pendidikan, 2022)
One source of learning in the learning process is learning materials. In distance education, learning resources prepared for students must be able to be studied independently. The separation of lecturers and students needs to be bridged by learning materials that can be understood by students. A video is a form of learning materials that can be used to help students understand the material. Through videos, students can learn anywhere and anytime according to the time available. In the video, the duration of the material delivery is very significant. Likewise, components such as intro, greeting, and outro greatly support student motivation. The effective video duration in learning website-based statistical data analysis is 10-15 minutes. The component of presenting material that is in great demand by students in the discussion of sample questions and their application using R software.